Diagnosis and follow-up MRI evaluation of tennis leg:New understanding of the pathogenesis and imaging. Issue 11 (November 2021) - Dai, Meng; Liu, Xi; Liu, Xiaoming; Yang, Lian; Duan, Deyu
Highlights: The injury of the medial head of gastrocnemius is more common than the plantaris tendon in patients with tennis leg. Fluid collection between the medial head of gastrocnemius and soleus is an important specific indication of tennis leg. Thickened reparative tissue at the distal myotendinous junction of the medial head of gastrocnemius is an indication of chronic tennis leg injury. Abstract: Objectives: To evaluate the Magnetic resonance imaging (MRI) findings of patients with a clinical diagnosis of tennis leg and to explore the pathogenesis of tennis leg. Methods: A retrospective review of 58 (45 men, 13 women; age range, 7–81 years; mean age, 46.7 years) patients with a clinical diagnosis of tennis leg at our hospital during a 64-month period (May 2014 through Sep 2019) was conducted. All patients underwent MRI scan. Follow-up MRI was performed on 4 patients. Images findings, including integrity of the myotendinous junction and tendon of the gastrocnemius and soleus, and presence of fluid collection were analyzed. Results: MRI revealed fluid collection between the medial head of the gastrocnemius and soleus in 44 cases (72.1%). In 25 cases (41.0%), the collected fluid spread to around the medial border of fascia cruris. Fifty-five cases (90.2%) had edema or disruption of the gastrocnemius, with most cases ( n  = 55) showing edema or disruption of the medial head of the gastrocnemius at the myotendinous junction. Twenty-two (36.1%) cases had edema or disruption of the soleus, with most cases ( n  = 17) showing edema or disruption of the soleus at the myotendinous junction. Plantaris tendon disruption was observed in 7 cases (11.5%). A thick area of reparative tissue at the distal myotendinous junction of the medial head of the gastrocnemius was observed in all 4 MRI patients followed up. Conclusion: Abnormalities of the medial head of the gastrocnemius at the myotendinous junction and tendon appear to be more common than those of the plantaris tendon. Reparative tissue at the distal myotendinous junction of the medial head of the gastrocnemius may be an important specific indication of chronic tennis leg injury.